Automatic hydroponic / Hanif Omar, Muhd Yazid Baharin and Muhd Akram Jamal - Omar, Hanif; Baharin, Muhd Yazid; Jamal, Muhd Akram (2015)
This report representing smart watering system that reduce human input in order to water the plant This project will automatically waters plant when sensor detect low moisture level at nurseries. It also will alerts user when water level at main tank is drop below necessary level. All function has been programed to the arduino to make sure all components like relay, and the sensor can operate completely. We are using ac 240 volts that run the arduino then detect humidity and water level also turn on buzzer and LED.